مقاصد الشريعة وأهميتها في االجتهاد - Husnul Haq (Institut Agama Islam Negeri (IAIN) Kediri, 2017)
Ijtihād is an important way to discover the law over new issues. The need for ijtihād in the present becomes even more important as the problem develops with the development of science and technology. Scholars (ulama) are urgently needed to discover the law over these new problems by using the correct method of ijtihād, by using texts without putting aside the reality of life and the intentions (maqāshid) behind those texts. This research aims to describe the urgency of maqāshid sharia in ijtihād. The study begins by explaining the meaning of ijtihād as well as maqashid sharia, and finally discovering the use of maqāshid sharia on the contemporary fatwas. The approach used in this research is descriptive-qualitative approach, because this study is intended to reveal and describe the meaning of ijtihād as well as maqāshid sharia, and the use of maqāshid sharia on those fatwas. By using research methods outlined above, it can be concluded that the maqāshid sharia have an important role in ijtihād. Therefore, the contemporary scholars relay on the maqashid sharia in their fatwas; in worship, transactions, family jurisprudence, modern medicine and others.